Magnetic Nanoparticles for Therapy and Diagnosis in Nanomedicine - Javier Bustamante Mamani; João Paulo Borges; Alexandre Malta Rossi; Lionel Fernel Gamarra (MDPI AG, 2023)
Magnetic nanoparticles (MNPs) have been widely used for their potential applications, mainly for the diagnosis and/or therapy (theranostic) of several diseases in the field of nanomedicine, as passive contrast agents, through the opsonization process, or active contrast agents, after their functionalization and the subsequent capture of the signal using various techniques such as magnetic resonance imaging (MRI), optical imaging, nuclear imaging, and ultrasound [...]